Oxford handbook of clinical pharmacy - Wiffen, Phil; Mitchell, Marc; Snelling, Melanie; Stoner, Nicola ([Oxford] : Oxford University Press, 2017)
Complementing the guidelines in the British National Formulary, this third edition remains the indispensable guide to clinical pharmacy providing all the information needed for practising and student pharmacists.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 29, 2017).
Keywords: Clinical pharmacology -- Handbooks, manuals, etc; Pharmacy -- Handbooks, manuals, etc